The mediating role of social support in self-management and quality of life in patients with liver cirrhosis - Ying Zhang; LeYao Xiao; Qian Liu; XinYi Zhang; MingDan Li; YaLi Xu; Mei Dai; Fei Zhao; YouShu Shen; Jordan Tovera Salvador; Ping Yang (Scientific Reports)
Abstract Patients with liver cirrhosis often experience factors such as malnutrition and lack of exercise, leading to reduced quality of life. Insufficient social support is related to self-management in patients with chronic diseases. Therefore, this study explores the mediating role of social support in the relationship between self-management and quality of life, analyzing the impact of exercise frequency and malnutrition risk assessment on social support, self-management, and quality of life. Using a convenience sampling method, cross-sectional data were collected from 257 patients with liver cirrhosis at the infectious disease department of a tertiary hospital in Zunyi, China, from 2021 to 2022. The patients were evaluated using a demographic questionnaire, the Self-Management Behavior Scale for Liver Cirrhosis Patients, the Social Support Rating Scale (SSRS), the Chronic Liver Disease Questionnaire (CLDQ), and the Royal Free Hospital Nutritional Prioritizing Tool (RFH-NPT). Data were analyzed using SPSS and PROCESS software. (1) Patients in the decompensated stage of liver cirrhosis and those classified in Child–Pugh class B/C had lower scores in self-management, quality of life, and social support compared to patients in the compensated stage of liver cirrhosis and those classified in Child–Pugh Class A. (2) Quality of life was positively correlated with both social support and self-management (r = 0.668, r = 0.665, both P < 0.001). (3) Mediation analysis showed that self-management had a direct predictive effect on quality of life. Social support had a mediating effect between self-management and quality of life, with an indirect effect of 0.489 (95% CI: 0.362, 0.629), accounting for 40.58% of the total effect. (4) Exercise frequency and malnutrition risk assessment were independent influencing factors for social support, self-management, and quality of life. (5) In the regression model, after excluding confounding factors, Model I explained 14% of the variance in quality of life due to control variables, Model II explained 49.5%, and when social support was added, Model III explained 56.9% of the variance in quality of life. Under the mediating role of social support, self-management can improve quality of life. Exercise frequency and malnutrition risk assessment, as independent influencing factors, also modulate social support and self-management. These findings underscore the importance of strengthening social support and developing self-management programs targeting exercise and nutrition to enhance the quality of life in patients with liver cirrhosis.